Persistent Opacification of the Woven EndoBridge Device: A Conebeam CT Analysis of the Bicêtre Occlusion Scale Score 1 Phenomenon - Caroff, J.; Popescu, S.D.; Mihalea, C.; Popica, D.A.; Ikka, L.; Gallas, S.; Ozanne, A.; Chalumeau, V.; Moret, J.; Cortese, J.; Spelle, L. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Some Woven EndoBridge devices present a persistent intradevice opacification at imaging follow-up, described as the Bicêtre Occlusion Scale Score 1 (BOSS 1) phenomenon. The clinical implications remain unknown. We aimed here to analyze the factors influencing this occurrence and to precisely describe the evolution of BOSS 1 with time using conebeam CT.MATERIALS AND METHODS: We retrospectively analyzed a prospectively maintained Woven EndoBridge database at our tertiary center and included all patients with isolated BOSS 1 and BOSS 1 associated with small neck remnant (BOSS 1 + 2).RESULTS: Two hundred sixty-seven aneurysms were treated with a Woven EndoBridge device between July 2012 and December 2021. Follow-up with DSA was available for 220 aneurysms (median, 5 months), among which BOSS 1 and 1 + 2 were found in 9.1% (20/220) (95% CI, 5.5%—12.7%). A second DSA follow-up (median, 17 months) was performed in 15 of these 20 aneurysms, which revealed that 40% had evolved to complete Woven EndoBridge occlusion, 33% showed a decreased persistent opacification, and 27% remained stable. BOSS 1 was significantly associated with postoperative antiplatelet medication, a lower aneurysm aspect ratio, and the use of the Woven EndoBridge 17 (P  < .05). The average Woven EndoBridge shape modification was less pronounced in the BOSS 1 population (P  < .02). None of the BOSS 1 or 1 + 2 aneurysms required retreatment or were associated with hemorrhage occurrence.CONCLUSIONS: Isolated persistent flow inside the Woven EndoBridge device at follow-up is rare and notably associated with antiplatelet prescription. It seems to present a benign course in most cases.BOSS 1Bicêtre Occlusion Scale Score 1CBCTconebeam CTFUfollow-upWShMWEB shape modificationWEBWoven EndoBridge